2015
DOI: 10.1186/s13068-015-0366-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel bifunctional GH51 exo-α-l-arabinofuranosidase/endo-xylanase from Alicyclobacillus sp. A4 with significant biomass-degrading capacity

Abstract: BackgroundImproving the hydrolytic performance of xylanolytic enzymes on arabinoxylan is of importance in the ethanol fermentation industry. Supplementation of debranching (arabinofuranosidase) and depolymerizing (xylanase) enzymes is a way to address the problem. In the present study, we identified a bifunctional α-l-arabinofuranosidase/endo-xylanase (Ac-Abf51A) of glycoside hydrolase family 51 in Alicyclobacillus sp. strain A4. Its biochemical stability and great hydrolysis efficiency against complex biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 50 publications
2
36
0
1
Order By: Relevance
“…For example, Yang and coworkers recently reported a bifunctional AFase from glycoside hydrolase (GH) family 51 that has the activity of both arabinofuranosidase and β-xylosidase. It worked synergistically with endoxylanase XynBE18 in the degradation of wheat arabinoxylan, increasing the production of sugar about 3-fold [5].…”
mentioning
confidence: 99%
“…For example, Yang and coworkers recently reported a bifunctional AFase from glycoside hydrolase (GH) family 51 that has the activity of both arabinofuranosidase and β-xylosidase. It worked synergistically with endoxylanase XynBE18 in the degradation of wheat arabinoxylan, increasing the production of sugar about 3-fold [5].…”
mentioning
confidence: 99%
“…xylobiose and xylooligomers. Acetyl xylan esterase is an accessory enzyme that functions synergistically with other enzymes in removing side chain residues from the hemicellulose backbone [50,51]. In the present study, four hemicellulases were identified, consisting of one arabinogalactan endo-β-1,4-galactanase (GH53) (1384349889), one beta-xylanase (GH43) (1384351325), one glucuronoxylanase (GH30) (1384349284), and one acetylxylan esterase (CE1) (1384350660) ( Table 3).…”
Section: Identification Of Secretomes Of B Velezensis Lc1 Grown On Mmentioning
confidence: 79%
“…A GH51 AFase from Alicyclobacillus sp. has also been reported to exhibit exoxylanase activity on soluble wheat arabinoxylan and sugar beet arabinan [45]. Wood and Macrae [46] reported that a GH62 AFase from Aspergillus awamori also showed the capacity to split off β-D-xylopyranosyl units from the main chain of arabinoxylan.…”
Section: Hydrolytic Products Analysismentioning
confidence: 98%